The Relationship Between Postpartum Mothers' Knowledge About Breast Care and The Incidence of Breast Milk Dam in Postpartum Mothers Days 3-6 in The Bps Area Mrs. Titik Ekawati, S.St Ds. Kintelan Kec. Puri Kab. Mojokerto - Titiek Idayanti; Rahma Fauziyah; Widya Anggraeni (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The emergence of dam milk at days 3-6 due to a lack of knowledge about the treatment of post partum mothers the right breast. The purpose of this study was conducted to know the relationship of maternal knowledge about postpartum care with the incidence of breast milk dam on postpartum days 3-6 in Region Connecticut District Puri Ny.Titik Ekawati, S.ST Village Kintelan Mojokerto regency. The design of this study using a cross sectional analytic methods. Its population is around 3-6 days post partum mothers who are in the BPS Ny.Titik Ekawati,S.ST the sample was 13 respondents residing in the territory of BPS Ny.Ekawati,S.ST, sampling is the accidental sampling technique, a variable of this study is the independent variable "knowledge of post-partum mothers about breast care "and the dependent variable" incidence of dam milk ". Data collected using questionnaires and observation Wilcoxon then tested and the results are presented in the form of a frequency distribution table. Results showed the majority (54%) of respondents whose knowledge is lacking, and almost half (46%) of respondents experienced dam milk and a small portion (8%) respondents who did not have dams milk. Wilcoxon test results obtained no knowledge of the relationship of maternal postpartum care with the incidence of breast milk dams on postpartum days 3-6 with a significance level α = 0.05 obtained significant number ρ = 0.036 which means that H1 is received.